Reliability evaluation of distribution systems considering automatic reclosers - Leite Da Silva, Armando M.; Cassula, Agnelo M. [UNESP]; Resende, Leonidas C.; Almeida, Ronaldo M.; Yamasaki, Mario T.; Paula, Gustavo M. F. (My University, 2004)
This paper presents a new methodology to evaluate in a predictive way the reliability of distribution systems, considering the impact of automatic recloser switches. The developed algorithm is based on state enumeration techniques with Markovian models and on the minimal cut set theory. Some computational aspects related with the implementation of the proposed algorithm in typical distribution networks are also discussed. The description of the proposed approach is carried out using a sample test system. The results obtained with a typical configuration of a Brazilian system (EDP Bandeirante Energia S.A.) are presented and discussed.
Keywords: Automatic recloser; Distribution reliability; Markovian models; Minimal cut sets; Power system reliability; Algorithms; Electric circuit breakers; Electric industry; Electric switches; Markov processes; Mathematical models; Problem solving; Real time systems; Reliability; Automatic reclosers; Electric power distribution